2007
DOI: 10.1080/15320380701741354
|View full text |Cite
|
Sign up to set email alerts
|

Modification to Imazaquin Degradation in Soil Amended with Farm Manure

Abstract: The effects of two farm manures, bovine manure (BM) and chicken manure (CM), on imazaquin degradation in a sandy loam soil were studied under laboratory conditions. The degradation of imazaquin in BM and CM-amended soil (10% by w/w) was about 2.4 and 1.5 times, respectively, faster than that in unamended soil. Different amendment ratios of BM to soil lead to different degradation rates of imazaquin. However, higher mix ratio did not necessarily increase the degradation, and the optimal active degradation of im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Our study also found that fertilizers applied at a normal field dose inhibited the dissipation of fipronil. Two other studies have reported that organic fertilizers accelerate the degradation of flubendiamide and imazaquin 50,51 …”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Our study also found that fertilizers applied at a normal field dose inhibited the dissipation of fipronil. Two other studies have reported that organic fertilizers accelerate the degradation of flubendiamide and imazaquin 50,51 …”
Section: Resultsmentioning
confidence: 96%
“…Two other studies have reported that organic fertilizers accelerate the degradation of flubendiamide and imazaquin. 50,51 Pesticide degradation commonly occurs via microbial aerobic degradation. 19,[23][24][25][26] In this study, the soil bacterial abundance and microbial communities were evaluated using the Shannon index, Chao 1 index, and microbial abundance analysis (Figs 2 and 3).…”
Section: Effect Of Fertilizers On Fipronil Dissipation In Soilmentioning
confidence: 99%
“…However, there is no specific relationship between the organic mat content and imidazolinone degradation based on this dataset, as shown in Figure 6. Sin a higher organic matter content tends to favor microbiological activity in the soil, Wan et al [43] evaluated its effect by incorporating 10% cattle manure into the soil, which In addition to soil texture, the organic matter content can also determine herbicide availability [42]. However, there is no specific relationship between the organic mat-ter content and imidazolinone degradation based on this dataset, as shown in Figure 6.…”
Section: 𝑡 = 𝑙𝑛 𝑙𝑛 2 𝑘mentioning
confidence: 99%
“…However, there is no specific relationship between the organic mat-ter content and imidazolinone degradation based on this dataset, as shown in Figure 6. Since a higher organic matter content tends to favor microbiological activity in the soil, Wang, et al [43] evaluated its effect by incorporating 10% cattle manure into the soil, which reduced the half-life of imazaquin from 21 to nine days.…”
Section: 𝑡 = 𝑙𝑛 𝑙𝑛 2 𝑘mentioning
confidence: 99%
“…The herbicide dissipated slightly faster in the sandy loam soil (soil 2) than in the clay soil (soil 1) ( Figure 3, Table 1). The degradation of imazaquin in soils has been mainly attributed to photodegradation and biological degradation (Ramezani et al, 2008;Wang et al, 2007b). In this work, the dissipation experiments were carried out in the dark, so that biodegradation may have been the major dissipation route for imazaquin.…”
Section: Dissipation In Unamended Soilsmentioning
confidence: 99%